2018
DOI: 10.3390/su10041037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Waste Brick Powder in the Mechanical Properties of Recycled Aggregate Concrete

Abstract: Brick and concrete are the main materials contributing to demolition and construction waste. Considering this precedent, the effects of using both residuals in medium strength concretes are analyzed. Waste brick powder is used as a cement replacement in three different levels: 5%, 10%, and 15%, and it is tested in concretes with no recycled aggregates and concretes with 30% of recycled coarse aggregates replacing natural ones. The compressive strength, the flexural strength, and modulus of elasticity are calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 48 publications
(62 reference statements)
2
40
0
Order By: Relevance
“…Standardization is needed in the building materials industry to ensure the quality of its products (Letelier et al, 2018;Seco et al, 2018). Essential aspects that must be present in bricks such as morphology, dimensions, and compressive strength are generally required to be realized.…”
Section: Design and Standardmentioning
confidence: 99%
“…Standardization is needed in the building materials industry to ensure the quality of its products (Letelier et al, 2018;Seco et al, 2018). Essential aspects that must be present in bricks such as morphology, dimensions, and compressive strength are generally required to be realized.…”
Section: Design and Standardmentioning
confidence: 99%
“…As a result, many studies have focused on reducing the environmental damages associated with its manufacturing. Several investigations have been based on one solution which is related to the study of the effects of substituting different concrete constituents with reused materials [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…There are some results that indicate the possibility of producing recycled concrete containing RCA or crushed bricks and used in the construction process where he explained that the presence of these materials within the concrete increases the compressive strength and therefore does not pose any risk in its use as a normal building material [14]. Letelier (2018) concluded that brick powder can be used in the concrete mix by 15% without a significant impact on concrete strength [15]. Marie (2017) found that through the use of RA and in different proportions can maintain the properties of mechanical and physical, concrete and thus can achieve sustainability using RA, but depends on the proportion of use within the concrete mix [16].…”
Section: Introductionmentioning
confidence: 99%